Comparación de dos métodos de medida del tiempo de ruptura lagrimal - Carrillo Sánchez, Melissa; Sánchez Alvarado, Úrsula Amanda (Universidad Antonio Nariño, 2024)
In 2017, the report carried out by the TFOS DEWS II was born with the purpose of giving conceptual order to dry eye disease (DED), which is closely related to the malfunction of the Tear Film (PL) and therefore affects the ocular surface (OS) (1).